Economic costs of ex ante regulations - Badri Narayanan; Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2020)
Regulations are an indispensable part of an economy and are proven to generate a significant impact on the economic, environment and social landscape. Through an extensive survey of literature and empirical study, the paper contrasts the benefits and costs arising in the light of the imposition of ex ante regulations of attempting to regulate a market sector, before a market failure has even occurred. It diverges from the norm of regulating ex-post, i.e. addressing market failures as they arise, which is the case in most modern open economies. The study highlights the economic impacts of shifting from ex post to ex ante in the online services sector as stipulated by the proposals for the Digital Services Act. It estimates a loss of about 85 billion EUR in GDP and 101 billion EUR in lost consumer welfare, due to a reduction in productivity, after accounting for other control variables. These costs are equivalent to losing all the gains that the EU has achieved to date from all its bilateral free trade agreements; or losing the contribution of passenger cars to the EU trade balance with the rest of the world. In the context of the pandemic-induced economic contraction, the GDP loss is equivalent to one-quarter of EU current account surplus projected for 2020. The extraordinarily high costs and rarity of ex ante rules warrant a discussion on the true objectives of the Digital Services Act. It is unclear which market failures it is envisaged to address - or how these failures can be so critical for the well-being for the European citizens, yet so irreparable and impossible to remedy ex post.
Keywords: 330; Regulierung; Kosten-Nutzen-Analyse; Marktversagen; Wirkungsanalyse; EU-Staaten